DIFFERENCES IN DIGITAL LITERACY OF FISHERMEN USING ONLINE MEETING APPLICATIONS BEFORE AND AFTER TEACHING AND MENTORING - hendra poltak; ismail ismail; Muhamad Ali ulat; muhfizar muhfizar (Jurnal Mantik, 2021)
The application of digitalization that has been developed massively has constraints, especially in human resources that have weaknesses in digital literacy and technical skills, as well as underdeveloped digital infrastructure. This makes the digital divide between regions, professions, social status, education and age, exacerbating inequality. As a result, the ease of the digital age such as work efficiency and effectiveness, increased economic productivity cannot be enjoyed which gets the digital divide. The study sample was 30 fishermen maladum Mes regency. The research method used is a pseudo-experimental method with the design of one group pretest-posttest. The results showed that there were differences in knowledge and skills of digital literacy practices after getting the intervention.